Em busca das dimensões que compõem a percepção do sistema de gestão de recursos humanos: Desenvolvimento e validação de um instrumento. - Ferreira, Ana Teresa (2015)
There is a call for more research efforts to uncover the processes moderating HRm and organizational results (Bowen and Ostroff, 2004; Becker & Gerhart, 1996). This research intends to adress this call and test the relationship between human resource management and affective organizational commitment. Recent research has emphasized the importance of moderators that intervene in this process, including organizational trust. Trust between supervisor and subordinate will be tested as a moderator of the dimensions of HRM. We performed a cluster analysis and a hierarchical regression analysis with interactions on 1328 employees and managers from 21 portuguese organizations. The analysis was performed on PASWS 18. The results show organizational trust as the most important predictor in affectice commitment. Two of the dimensions of HRM have direct effect on commitment. Our results also show an interaction between trust and distributive justice.